Az ipari recesszió és következményei Közép- és Kelet-Európában (1929-1933) = The consequences of industrial recession in Central and Eastern Europe (1929-1933) - Domonkos, Endre (Közép-Európai Közlemények, 2018)
The world economic crisis, which started in the field of agriculture in Central and Eastern Europe had profound impacts on the industry as well. Because most of countries in the region were specialized in exporting agricultural products, the consequences of industrial recession were completely different in Central and Eastern Europe. The objective of my essay is to evaluate the effects of economic crisis in the industry of seven Central and Eastern European countries (Austria, Czechoslovakia, Poland, Hungary, Romania, Bulgaria and Yugoslavia). As a consequence of developed export and industrial capacities the industrial recession was severe in Austria and in Czechoslovakia, while its impacts were limited in the Balkan countries. Because of limited extent I wouldn’t like to deal with the crisis management measures, which were introduced in Central and Eastern Europe.